Bullying victimization and suicide ideation and behavior among adolescents in Europe: a 10-country study - Barzilay, Shira; Brunner, Romuald; Kaess, Michael (Journal of adolescent health, 2017)
Purpose: To examine risk and protective factors moderating the associations between three types of bullying victimization (physical, verbal, and relational bullying) with suicide ideation/attempts in a large representative sample of European adolescents. Methods: We analyzed cross-sectional data on 11,110 students (mean age = 14.9, standard deviation = .89) recruited from 168 schools in 10 European Union countries involved in the Saving and Empowering Young Lives in Europe study. A self-report questionnaire was used to measure victimization types, depression, anxiety, parental and peer support, and suicide ideation and attempts. For each outcome, we applied hierarchical nonlinear models controlling for sociodemographics. Results: Prevalence of victimization was 9.4% physical, 36.1% verbal, and 33.0% relational. Boys were more likely to be physically and verbally victimized, whereas girls were more prone to relational victimization. Physical victimization was associated with suicide ideation, and relational victimization was associated with suicide attempts. Other associations between victimization and suicidality (ideation/attempts) were identified through analysis of interactions with additional risk and protective factors. Specifically, verbal victimization was associated with suicide ideation among adolescents with depression who perceived low parental support. Similarly, low peer support increased the associations between verbal victimization and suicide ideation. Verbal victimization was associated with suicide attempts among adolescents with anxiety who perceived low parental support. Conclusions: Findings support the development of prevention strategies for adolescent victims of bullying who may be at elevated risk for suicide ideation/behavior, by taking into account gender, the type of bullying, symptomatology, and availability of interpersonal support.